English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

ln x + ln(y^2) = 3

2007-10-10 22:53:49 · 3 answers · asked by i<3WL 2 in Science & Mathematics Mathematics

3 answers

(1/x) + (1/y^2)(2y)y' = 0
(2 / y)y' = -(1/x)
y' = (-1/x)(y/2)
y' = -y / 2x

2007-10-10 23:02:28 · answer #1 · answered by Mathematica 7 · 0 0

i propose to pass from the logarithm to power
remember lna+ln b= ln ab
first remark that x must be positive else no log

so lnxy^2 = lne^3

xy^2 = e^3

y = e^3/2 /x^1/2

dy/dx= -1/2 *e^(3/2)*x^(-3/2) or -1/2 *e^(3/2) /(x^3)^0.5

2007-10-10 23:08:48 · answer #2 · answered by maussy 7 · 0 0

lnx + ln(y^2) = 3
hence

lnx + 2lny = 3

no differentiating with respect to x , we get :

1/x + (2/y)dy/dx = 0

hence

dy/dx = -y/2x

2007-10-10 23:07:35 · answer #3 · answered by Sagar 2 · 1 0

fedest.com, questions and answers